2013
DOI: 10.1371/journal.pone.0080420
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Mass Sociogenic Illness in a School Feeding Program in Northwest Bangladesh, 2010

Abstract: BackgroundIn 2010, an acute illness outbreak was reported in school students eating high-energy biscuits supplied by the school feeding programme in northwest Bangladesh. We investigated this outbreak to describe the illness in terms of person, place and time, develop the timeline of events, and determine the cause and community perceptions regarding the outbreak.MethodsWe defined case-patients as students from affected schools reporting any two symptoms including abdominal pain, heartburn, bitter taste, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…Similar finding was reported from Kombolcha of Northern Ethiopia, Derashe of Southern Ethiopia, [17][18]. On the other hand toxic chemicals and environmental pollution have been notified in western setting; India due to toxic fumes [13], these attributions in Africa, lead many victims commonly seek treatment from different religious and traditional healing sites [13][14][15][16][17][18]. This is also practice in Ethiopia context in which more than half (63.9%) of study participants in Derashe district of Southern Ethiopia reported that they had been visiting traditional healing services, 8.2% had sought treatment from religious services, 75.3% modern health service, 5.1%, all the three treatment sites, namely traditional healers, religious healers and health institutions [18].…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Similar finding was reported from Kombolcha of Northern Ethiopia, Derashe of Southern Ethiopia, [17][18]. On the other hand toxic chemicals and environmental pollution have been notified in western setting; India due to toxic fumes [13], these attributions in Africa, lead many victims commonly seek treatment from different religious and traditional healing sites [13][14][15][16][17][18]. This is also practice in Ethiopia context in which more than half (63.9%) of study participants in Derashe district of Southern Ethiopia reported that they had been visiting traditional healing services, 8.2% had sought treatment from religious services, 75.3% modern health service, 5.1%, all the three treatment sites, namely traditional healers, religious healers and health institutions [18].…”
Section: Introductionsupporting
confidence: 72%
“…Among the total reported hospitalized ill students in Bangladesh, 88% complain about consumption of cake with abnormal smell or taste. Among these, 20% of them felt ill by only seeing other ill students in the school [16]. Satanism and evil devil force, punishment by God, due to the presence of toxic chemicals, polluted environment, cold air, and using family planning injection or pills had been discovered around the schools and community members in Ethiopia [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of these attribution styles, in Africa, many victims of MPI commonly seek treatment from religious and traditional healing sites [5, 12, 13]. Though there is no conclusive evidence about the causes of MPI, the following are postulated causes: psychological factors, environmental factors, different stressors, conflicts, lower level of education, lower socioeconomic status, minority race, and history of abuse or trauma [1719]. …”
Section: Introductionmentioning
confidence: 99%